Penerapan Hukum dan Hakam Adat Sumbang Salah di Kelurahan Dusun Baru Kecamatan Tabir Kabupaten Merangin - Setyoko, Joko; Badrun, Badrun (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
This study aims to determine the application of wrong discordant customary law and hakam in Dusun Baru Village, Tabir District, Merangin Regency. To find out the obstacles faced in the application of wrong discordant customary law and rights in Dusun Baru Village, Tabir District, Merangin Regency. As well as to find out the efforts of traditional institutions to overcome obstacles in the application of wrong discordant customary law and rights in Dusun Baru Village, Tabir District, Merangin Regency. In this research, the location is Dusun Baru Village, Tabir District, Merangin Regency. The reason for choosing this location is because the researcher sees that the Rantau Panjang Inner is the largest mind in Tabir District and still maintains customary laws and rights. This research was carried out from January to March 2021. The results showed that the application of discordant customary law and hakam in Dusun Baru Village Tabir District, Merangin Regency where violations of this provision were subject to a maximum fine of one chicken, one bushel of rice and one coconut. , and the height of a goat, forty (40) bushels of rice and a sack of cloth. Constraints faced in the application of wrong discordant customary law and hakam in Dusun Baru Village, Tabir District, Merangin Regency, have a low level of public awareness of obedience to customary rules, especially the younger generation. Efforts by traditional institutions to overcome obstacles in the application of wrong discordant customary law and hakam in Dusun Baru Village, Tabir District, Merangin Regency include Approaching the Community and Recording Customary Law and Hakam.